Política de línguas e mídia no Mercosul: um estudo enunciativo de jornais de fronteira - Weber, Andréa Franciéle (2013)
This work investigates the functioning of the politician in saying “in” and “about the” languages in newspapers from the platinum border, with a view to a politics of languages of media in Mercosul. For this, we took as corpus nine newspapers published in different cities of Brazilian border, such as Uruguay and Argentina, analyzing the way the Portuguese, Spanish and Guarany languages, which are the ones recognized by the bloc, are employed and thematized in the news construction. The saying-in and about-the languages subscribed in these newspapers project in the platinum social imaginary a political distribution of these languages as global, of regional integration, national and local, configuring a politics of languages in the media. As analytical device, the study mobilized the designation category, taken from the perspective of the Happening Semantics and the Enunciation Linguistics. As an additional support, we used historical and special editions from border newspapers, already extinct or in circulation, besides the interviews with editors, writing bosses and journalists from these newspapers. Divided in five chapters, this dissertation, explores, on the first chapter, the politics of languages in media ; on the second, the functioning of the Portuguese, Spanish and Guarany languages as global, of regional integration, national and local in the platinum countries; on the third, the particularities of media from the platinum border; on the fourth, the politics of languages in the global, national and border media; on the fifth and last chapter, the political distribution of Spanish, Portuguese and Guarany languages in the constitution of one saying-in and about-the languages in border newspapers. The results show that these newspapers mobilize the patterning Spanish and Portuguese languages for the news composition, distributing them in the news space, according to theme and the target public. The presence of these languages as the news’ theme is non frequent and co-star, frequently related to the educational area. As much in the saying-in as in the sayingabout- the languages, Spanish and Portuguese obey to a political distribution which situates them as national from platinum countries. These languages are inscribed as nations’ identifying elements in the context of regional integration.